Manajemen Pembinaan Santri Dalam Mengembangkan Jiwa Kewirausahaan - Ade Riana; Ahmad Sukandar; Marwan Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to observe and analyze how the process of planning, implementing, evaluating activities and supporting and inhibiting factors. In this study, the researcher used a qualitative approach with a case study design. Data collection techniques through interviews, observation and documentation. Data analysis techniques include data redaction, data presentation and conclusion drawing. The findings from the field: 1). The planning is in the early stages, incorporating entrepreneurship learning into the curriculum (extracurricular), selecting business fields according to the talents and interests of students, providing knowledge about the methods or methods developed by the Prophet Muhammad and instilling the value of honesty 2). The implementation is by providing scholarships for students who are economically disadvantaged and also in addition to students being given religious and entrepreneurial material, they are told to practice by going directly into the field according to their talents and interests 3). Evaluation, namely self-confidence, obedience, obedience, discipline and respect for time, high enthusiasm for abilities and expertise, a sense of independence, more trust and honesty, students have their own income, can balance spiritual and financial (ukhrowi and worldly) 4). Inhibiting factors include: The public view that pesantren is not to produce entrepreneurs but to produce scholars, the lack of human resources, equipment, raw materials and capital/finance of pesantren. Supporting factors are strong motivation from the leadership of a kyai and the existence of entrepreneurship lessons